Técnica do Grupo de Renormalização Numérico (GRN) aplicada em quantum dots - Martin, João Gabriel [UNESP] (2014)
In this paper, we review the technique of numerical renormalization group (NRG) originally introduced to study the properties of correlated systems. Besides the revision stage of this study, we apply the to NRG calculus of the conductance quantum dots considering two con gurations, depending on the disposition towards the electrodes.In the rst the dot is located between two metal electrodes and in the second the quantum dot is laterally connected to a conductor wire. Theoretical models have been introduced to describe the process of electron transport through quantum dots, as well as allowed to establish basic theoretical relationships between the conductance and the parameters of the model Hamiltonian. With the numerical diagonalization by renormalization group, we calculate the conductance through the eigenvalues and eigenvectors. We also managed to analytically calculate the conductance for the two arrangements of quantum dots considered and con rm the numerical results obtained. Finally, this study allowed physically comprise the conduction of electrons through quantum dots as well as attest the e ciency of the technique of renormalization